(untitled) (Advancements in Homeopathic Research, 2022)
Background: Autism is a neuro-developmental disorder that is characterized by impairment of the ability of communication and social interaction. It is commonly referred to as Autism Spectrum Disorder. The article tries to share the experience of the author dealing with autistic patients in the clinical practice, their unpleasant aura along with the importance of mother’s history during pregnancy that has an effect on the child, and the homoeopathic approach including the supportive treatment as well. All the above mentioned aspects collectively help a homoeopath to confidently manage such cases.